STRATEGI PENETAPAN HARGA MELALUI PERHITUNGAN BIAYA PRODUKSI PADA UMKM VANDEL RYAN - Suwari, Kharisma Isna; Rahma, Lina; Fitriana, Noor Laila (UNIVERSITAS DHARMAWANGSA, 2024)
Cost accounting is an important element that must be calculated carefully when making a product. The cost of production is the most important part of the production calculation process, because it contains cost information needed during production. One method that can be used to calculate production costs is the variable costing method which includes direct raw material costs, direct labor costs, and variable factory overhead costs. UMKM Vandel Ryan is a business that operates in the woodworking sector and the author wants to know ho to calculate production costs using the variable costing method.